2019
DOI: 10.1074/jbc.ra118.006583
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol exposure reduces serotonin receptor 1A internalization by increasing ubiquitination and degradation of β-arrestin2

Abstract: Acute alcohol exposure alters the trafficking and function of many G-protein-coupled receptors (GPCRs) that are associated with aberrant behavioral responses to alcohol. However, the molecular mechanisms underlying alcohol-induced changes in GPCR function remain unclear. ␤-Arrestin is a key player involved in the regulation of GPCR internalization and thus controls the magnitude and duration of GPCR signaling. Although ␤-arrestin levels are influenced by various drugs of abuse, the effect of alcohol exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…To maintain stable ethanol levels during the treatment, cell plates were placed within a closed polypropylene box alongside an open culture dish of a matching ethanol concentration. We previously reported a minimal loss of ethanol (3.13 ± 0.85%) over 18 h under this treatment condition (Luessen et al, 2019).…”
Section: Methodsmentioning
confidence: 53%
See 3 more Smart Citations
“…To maintain stable ethanol levels during the treatment, cell plates were placed within a closed polypropylene box alongside an open culture dish of a matching ethanol concentration. We previously reported a minimal loss of ethanol (3.13 ± 0.85%) over 18 h under this treatment condition (Luessen et al, 2019).…”
Section: Methodsmentioning
confidence: 53%
“…We previously reported a minimal loss of ethanol (3.13 ± 0.85%) over 18 h under this treatment condition (Luessen et al, 2019).…”
Section: N2a-5-ht1ar Cellsmentioning
confidence: 58%
See 2 more Smart Citations
“…We observed that the mRNA of Uqcrc 2 was unchanged in ethanol-induced injury livers, while UQCRC2 protein levels decreased in injured livers. UQCRC2 can be degraded by ubiquitylation [ 35 , 36 ], and ethanol can cause a high ubiquitylation level of protein [ 37 ]. The qRT-PCR results showed that AMPK significantly enhanced the Uqcrc2 fold change numbers.…”
Section: Resultsmentioning
confidence: 99%